PERANCANGAN APLIKASI MONITORING TERHADAP KINERJA MURID SEKOLAH DASAR DAN MENENGAH PERTAMA - Surja, Stephanie; Veronica, Veronica; Muryono, Tupan Tri (ISTEK WIDURI, 2023)
The process of exchanging information between schools and parents can affect the process of children's educational performance, especially the role of the family, because the family is the person who influences the child's development. However, not a few parents are busy at work, especially career parents who have children so that a good communication process can be neglected. This is a concern for the author to bridge the exchange of information between schools, children and parents so that there is no distance that can lead to errors or information about children at school so that parents can continue to monitor the development of children's education using the platform that the author created anytime and anywhere. The purpose of this research is to help link information about children's development at school not to stop or stop in the school environment, but parents can also participate in knowing the activities their children are doing at school by monitoring their children's performance or performance at school through a platform that can be accessed easily. especially for students at the elementary level, namely elementary and junior high schools because basic education is a general indicator that can be used to see the level of intelligence of the nation. The method that the author uses to carry out system analysis and design is application design using the System Development Life Cycle (SDLC). The results of this research are monitoring applications that are made to make it easier for the school to carry out teaching and learning activities as well as parents who monitor the development and activities of their children at school. It can facilitate access to exchange of information from school to parents and vice versa so that there are no gaps or miss information with parents and easily see the number of students, value recap, and student spp payment reports. parents are also very helpful because they can easily monitor their child's performance at school, both academic and non-academic, parents can also consult with relevant teachers if their child has problems at school and parents can also see the daily agenda and will also get notifications about the status of tuition payments.